Strategy of Improving Wheat (Triticum aestivum L.) Productivity under New Alluvial Zone through Demonstration Programme - Mukherjee , Dhiman (Indian Journal of Extension Education, 2019)
The front line demonstrations of wheat were conducted during the rabi season of 2014-17 in seventeen farmers fields to demonstrate production potential and economic benefit of improved technologies consisting suitable variety (viz. HD 2967), improved nutrient (150:60:40 kg/ha NPK) and weed control measures under new alluvial zone of West Bengal, in irrigated conditions. The productivity of wheat ranged from 32.95 to 38.43 q/ha with mean grain yield of 36.13 q/ha under improved practice on farmers field as against a grain yield under farmers practice which ranged from 21.98 to 24.65 q/ha with a mean of 23.36 q/ha. It is evident from the results that the yield of improved wheat variety was found better than the local check under same environmental conditions. Farmers were motivated by results of demonstrated technologies applied in the FLDs and it is anticipated that they would adopt these technologies. Yield of the front line demonstration and potential yield of the crop was compared to estimate the yield gaps which were further categorized into technology index. Cultivation of wheat under improved practices fetch higher net return of Rs. 19,519 to Rs. 23,247/ha compared to farmer practice of Rs. 7,847 to Rs.12,100/ha. The average B: C ratio of improved technology was 1.77 in comparison of farmer practice mean B: C ratio was 1.43.
Keywords: FLD; Improved practice; Variety; Wheat; Yield